O papel das interações polêmicas (controvérsias científicas) na construção do conhecimento biológico: investigando um curso de formação continuada de professores sobre evolução humana - Bulla, Marcelo Erdmann (2016)
The research presented here is focused on the Human Biological Evolution, its Polemic Interactions (scientific controversies) and Continued Formation of teachers. We aim to highlight the role of polemic interactions in the construction of biological knowledge by polemic among paleoanthropologists Tim White and Esteban Sarmiento on the hominid fossil Ardipithecus ramidus ("Ardi"). We also propose to evaluate the development of a teaching sequence about the subject, in a continued formation course for teachers of science and biology of basic public network Cascavel-PR and region. We justify the choice of the theme "human biological evolution" because it is a area little or anything addressed during the initial formation (graduation) and in the absence of continued formation courses. The decision in research on polemic interactions ocurred due to the fact that these are the natural dialogical context of science in which are elaborated theories. The choice of White-Sarmiento polemic interaction is justified due this scientific controversy proposes a revision of two hypotheses relatively well accepted by the scientific community: "savannah hypothesis" and the "hypothesis chimpanzee-like common ancestor". In addition, we have already used simplified way this polemic in high school resulting in fruitful discussions about science. Such polemic interaction was analyzed according to the criteria established by the philosopher Marcelo Dascal (1994; 2005; 2006) and classified as the dominant type discussion. The empirical work involved collecting data from the answers provided by teachers to an initial questionnaire and a final. In addition to the questionnaires, we collect data from filming during the formation course. The data made were evaluated by Content Analysis methodology. The analysis and discussion of data obtained from empirical research with teachers has highlighted the urgency and relevance in proposing at least one elective course that addresses human biological evolution in the initial formation. However, we hope that such content should be included in compulsory subject. Sets up also of utmost urgency offering continued formation courses in the area for teachers already inserted at schools. We also evidenced the importance of polemic interactions for the development and advancement of scientific knowledge. We conclude that teaching biology and science using polemic interactions (scientific controversies) may be in satisfactory teaching tool to present the history of science and it nature, since scientific activity is permeated by conflicts and intellectual battles. Present this scientific image can improve the understanding of students in relation to the internal operating mode of science within the scientific communities, highlighting its competitive and collective character. Some teachers realized the presence of non-scientific values in White-Sarmiento scientific controversies. This is important to remind us not to introduce to students the scientist's image as someone alien to society and culture